Posisi Islam Pesantren dalam Pluralisme Agama: Studi Kasus Pesantren Lirboyo Kediri: The Position of Islamic Boarding Schools in Religious Pluralism: A Case Study of Lirboyo Islamic Boarding School, Kediri - Muniron Muniron (Fenomena, 2007)
This research examines the position of Pesantren Islam in the context of religious pluralism, focusing on doctrinal and methodological potentials that may lead to intolerant or tolerant behavior. It is based on the classification of normative-doctrinal Islam and empirical-historical Islam. The aim is to describe and analyze the position of Pesantren Islam, both doctrinally and in its approach to study, in responding to religious pluralism. The research employs a qualitative approach with a case study design at Pesantren Lirboyo Kediri. Data were collected through interviews, observation, and document study, then analyzed using an induction-interpretation-conceptualization model. The results show that, doctrinally, discriminatory texts against non-Muslims are present, and, methodologically, the Islamic study approach is predominantly theological. However, because Islam is understood contextually and comprehensively, based on core Islamic values, these negative potentials are not actualized. Instead, the pesantren demonstrates tolerant and accommodative behavior toward followers of other religions. In conclusion, the position of Pesantren Islam Lirboyo supports a conducive atmosphere for religious pluralism in Kediri, and strengthening a contextual approach in the study of classical Islamic texts is recommended. Penelitian ini membahas posisi Islam pesantren dalam konteks pluralisme agama, dengan fokus pada potensi doktrinal dan metodologis yang dapat melahirkan perilaku intoleran atau toleran. Penelitian ini didasarkan pada kerangka klasifikasi Islam normatif-doktrinal dan Islam empiris-historis. Tujuannya adalah mendeskripsikan dan menganalisis posisi Islam pesantren, baik dari aspek doktrin maupun pendekatan studinya, dalam merespons realitas pluralisme agama. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus di Pesantren Lirboyo Kediri. Data dikumpulkan melalui wawancara, observasi, dan studi dokumen, lalu dianalisis dengan model induksi-interpretasi-konseptualisasi. Hasil penelitian menunjukkan bahwa secara doktrinal ditemukan teks-teks diskriminatif terhadap non-muslim, dan secara metodologis pendekatan studi Islam lebih bersifat teologis. Namun, karena Islam dipahami secara kontekstual dan komprehensif berdasarkan nilai-nilai dasar Islam, potensi negatif tersebut tidak teraktualisasi. Sebaliknya, pesantren menunjukkan perilaku toleran dan akomodatif terhadap pemeluk agama lain. Kesimpulannya, posisi Islam Pesantren Lirboyo mendukung terciptanya suasana kondusif bagi pluralisme agama di Kediri, dan direkomendasikan penguatan pendekatan kontekstual dalam studi kitab kuning.